Enlaces - Becker Ravest, Alex (AUS - Arquitectura / Urbanismo / Sustentabilidad, 2017)
http://www.sostenibilidad.com http://www.pactomundial.org http://www.agua-dulce.org http://www.profesiones.org http://www.allweneed.lu/Footprint